Pemberdayaan Generasi Z melalui Pelatihan Investasi Keuangan Digital dan Kompetisi Trading - Handayani, Kristin; Fuad, Muhammad (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
The "Investing Competition" activity was carried out in order to improve financial literacy among students in particular and the younger generation in general. The initial survey of the activity found a low level of financial literacy among generation Z students, so efforts were needed to provide a better understanding of investment. Through interactive training and virtual trading competitions for 2 (two) months, participants experienced a significant increase in their understanding of investment, with an average pre-test score increasing from 55 before the training to 80 after the training. Despite obstacles, such as time constraints, differences in knowledge background, and geographical distance, the participants showed high enthusiasm. The trading competition attended by various universities not only provided practical experience, but also encouraged participants to learn from their mistakes and share strategies with fellow students, as well as creating a mutually supportive learning community. The results of this activity show the potential of the younger generation as smart investors, as well as the importance of financial education in building financial independence. The conclusion of this activity highlights the success of the methods used and provides suggestions for the development of similar activities in the future, such as increasing the duration of training and post-activity support in a special community. It is hoped that this initiative will contribute to better economic development, especially for the younger generation.